N-[1,3-Dialkyl(aryl)-2-oxoimidazolidin-4-ylidene]-aryl(alkyl)sulphonamides as Novel Selective Human Cannabinoid Type 2 Receptor (hCB2R) Ligands; Insights into the Mechanism of Receptor Activation/Deactivation - Gianquinto, Eleonora; Sodano, Federica; Rolando, Barbara; Kostrzewa, Magdalena; Allarà, Marco; Mahmoud, Ali Mokhtar; Kumar, Poulami; Spyrakis, Francesca; Ligresti, Alessia; Chegaev, Konstantin (Molecules (Basel, Switzerland), 2022)
Cannabinoid type 1 (hCB1) and type 2 (hCB2) receptors are pleiotropic and crucial targets whose signaling contributes to physiological homeostasis and its restoration after injury. Being predominantly expressed in peripheral tissues, hCB2R represents a safer therapeutic target than hCB1R, which is highly expressed in the brain, where it regulates processes related to cognition, memory, and motor control. The development of hCB2R ligands represents a therapeutic opportunity for treating diseases such as pain, inflammation and cancer. Identifying new selective scaffolds for cannabinoids and determining the structural determinants responsible for agonism and antagonism are priorities in drug design. In this work, a series of N-[1,3-dialkyl(aryl)-2-oxoimidazolidin-4-ylidene]-aryl(alkyl)sulfonamides is designed and synthesized and their affinity for human hCB1R and hCB2R is determined. Starting with a scaffold selected from the NIH Psychoactive Drug Screening Program Repository, through a combination of molecular modeling and structure–activity relationship studies, we were able to identify the chemical features leading to finely tuned hCB2R selectivity. In addition, an in silico model capable of predicting the functional activity of hCB2R ligands was proposed and validated. The proposed receptor activation/deactivation model enabled the identification of four pure hCB2R-selective agonists that can be used as a starting point for the development of more potent ligands.